4D Seismic Feasbility of Central Luconia FOT Field - Zanuri, M.N.A. (Asian Research Publishing Network, 2019)
Complex pore component in carbonate reservoirs are due to their susceptibility toward diagenesis. The secondary pores created such as fractures, vugs and moldic have known to alter the sonic velocity propagation thus, produce a complex seismic response. This become a basis in pore type quantification utilizing Xu-Payne rock physics method (XP) where the distribution of these pore types are able to be separated into stiff, intergranular and soft pores. XP are applied on the well data of FOT and on seismic arbitraiy line using pre-stack inversion. With the known pore types, the reservoir conditions of FOT are manipulated to give a new elastic modulus and are being shown in terms of seismic generation. The changes of Direct Hydrocarbon Indicators (DHI) supported by amplitude differences and polarity are observed in the results when the Gas Water Contact (GWC) are manipulated thus indicating a good 4D feasibility results for FOT carbonate reservoirs. Â© 2019 Medwell Journals. All Rights Reserved.